2013
DOI: 10.1093/reep/res016
|View full text |Cite
|
Sign up to set email alerts
|

The Porter Hypothesis at 20: Can Environmental Regulation Enhance Innovation and Competitiveness?

Abstract: CIRANO Le CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Le financement de son infrastructure et de ses activités de recherche provient des cotisations de ses organisations-membres, d'une subvention d'infrastructure du Ministère du Développement économique et régional et de la Recherche, de même que des subventions et mandats obtenus par ses équipes de recherche. CIRANO is a private non-profit organization incorporated under the Québec Companies Act. Its infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
650
3
19

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,140 publications
(694 citation statements)
references
References 58 publications
22
650
3
19
Order By: Relevance
“…This partly overlaps with the so-called Porter hypothesis (Porter and van der Linde 1995) even though evidence of this hypothesis is still inconclusive and subject to fierce debate and different interpretations (Ambec et al 2013). More important in this context is the suggestion that urban and regional policies often run ahead of national and supranational regulations in their response to climate change, which provides additional fuel to the argument that the formation of sustainability transition pathways unfolds in a geographically uneven way.…”
Section: Suggestions For Future Researchmentioning
confidence: 90%
“…This partly overlaps with the so-called Porter hypothesis (Porter and van der Linde 1995) even though evidence of this hypothesis is still inconclusive and subject to fierce debate and different interpretations (Ambec et al 2013). More important in this context is the suggestion that urban and regional policies often run ahead of national and supranational regulations in their response to climate change, which provides additional fuel to the argument that the formation of sustainability transition pathways unfolds in a geographically uneven way.…”
Section: Suggestions For Future Researchmentioning
confidence: 90%
“…Reasons for this include the creation of a level playing field, decreased uncertainty over investment choices, and the articulation of companies' visions. A meta-study on Porter's hypothesis concluded that stricter regulation indeed leads to more innovation, but that the overall influence on business performance is rather mixed (Ambec et al 2013). The picture of the impact of regulation on innovation becomes even more diffuse when taking differences in sector, time horizon, company characteristics and type of regulation into account (Blind 2012).…”
Section: Policy Learningmentioning
confidence: 99%
“…Many CO 2 abatement options are in fact net present value (NPV) positive and would increase the value of the firm undertaking the investment (Figure 1). This is a variation of the famous Porter Hypothesis that claims that strict environmental regulation may help firms tap new sources of competitive advantage [17,18]. Porter argues that firms, in violation of economists' common assumption of efficiency, do not implement existing technological solutions although, given current prices and interest rates, investments are attractive.…”
Section: Introductionmentioning
confidence: 99%